2021
DOI: 10.1111/pce.14156
|View full text |Cite
|
Sign up to set email alerts
|

A clear trade‐off between leaf hydraulic efficiency and safety in an aridland shrub during regrowth

Abstract: It has been suggested that a trade‐off between hydraulic efficiency and safety is related to drought adaptation across species. However, whether leaf hydraulic efficiency is sacrificed for safety during woody resprout regrowth after crown removal is not well understood. We measured leaf water potential (ψleaf) at predawn (ψpd) and midday (ψmid), leaf maximum hydraulic conductance (Kleaf‐max), ψleaf at induction 50% loss of Kleaf‐max (Kleaf P50), leaf area‐specific whole‐plant hydraulic conductance (LSC), leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…For example, H. ammodendron has a low efficiency (lower K max ) but strong resistance to embolism (i.e., more negative P 50 ), whereas A. bracteata exhibits the opposite trend, which is likely owing to their leaf and canopy structure characteristics (e.g., large crown size and leaf degeneration in H. ammodendron , but larger leaf area and leathery leaves in A. bracteata ) or differences in xylem anatomy, which merits further study. Our results are consistent with previous investigations that suggest strong trade-offs between hydraulic safety and efficiency within numerous single sites ( Martınez-Vilalta et al., 2002 ; Pratt et al., 2007 ) and among particular taxa ( Hacke et al., 2007 ; Yao et al., 2021 ). The relationships among traits at the global scale do not necessarily manifest similarly at specific sites or in a specific region—traits that appear closely coordinated at certain scales may have different sensitivities to scale-dependent drivers of variation ( Messier et al., 2017 ), which may be attributed to species evolving different life history traits (physiological and morphological traits) in different environments ( Xu et al., 2007 ; Gupta et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…For example, H. ammodendron has a low efficiency (lower K max ) but strong resistance to embolism (i.e., more negative P 50 ), whereas A. bracteata exhibits the opposite trend, which is likely owing to their leaf and canopy structure characteristics (e.g., large crown size and leaf degeneration in H. ammodendron , but larger leaf area and leathery leaves in A. bracteata ) or differences in xylem anatomy, which merits further study. Our results are consistent with previous investigations that suggest strong trade-offs between hydraulic safety and efficiency within numerous single sites ( Martınez-Vilalta et al., 2002 ; Pratt et al., 2007 ) and among particular taxa ( Hacke et al., 2007 ; Yao et al., 2021 ). The relationships among traits at the global scale do not necessarily manifest similarly at specific sites or in a specific region—traits that appear closely coordinated at certain scales may have different sensitivities to scale-dependent drivers of variation ( Messier et al., 2017 ), which may be attributed to species evolving different life history traits (physiological and morphological traits) in different environments ( Xu et al., 2007 ; Gupta et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Leaf vein density and conduit diameter are two characteristics of the xylem that are closely connected to leaf hydraulic efficiency [84]. Leaf water potential and hydraulic conductivity are negatively correlated, and hydraulic conductivity increases with leaf age [19]. Furthermore, leaf hydraulic safety is influenced by the characteristics of the tissues outside the xylem, such as the turgor loss point, and by the vein xylem's characteristics, such as vein structure [85].…”
Section: Leafmentioning
confidence: 99%
“…Previous studies have shown that more efficient xylem comes at the cost of being more vulnerable to hydraulic failure [14,[17][18][19]. Nevertheless, whether there is a general tradeoff between hydraulic safety and efficiency remains controversial, and there is growing evidence that this trade-off might only exist in some cases or be weak [13].…”
Section: Introductionmentioning
confidence: 99%
“…This may have been because the greater the index of abundance, the greater the number of species, and the more complex water-use and water-sharing strategies that exist between species, the easier it is for species to survive. In the past, researchers have studied the factors that affect the resistance and resilience of individual species [2,5,7,8,12,13,16,19,[21][22][23][24]44], but few have studied the factors that affect the resistance and resilience of communities. Different communities have different characteristics of species composition, structure, and diversity.…”
Section: Factors Influencing Resistance and Resilience Of The Shrub C...mentioning
confidence: 99%